Model Administrasi Pengadaan Sarana dan Prasarana Pendidikan di Sekolah Dasar Islam Terpadu Future Islamic School - Mega Utami Imyansah; Sriwahyuni Sriwahyuni; Rifka Andriani; Hanna Sajiddah; Yohana Dwi Putri; Sakban Sakban (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
study aims to know, study, explore and describe the administrative model of procurement of educational facilities and infrastructure in elementary schools more organized and efficient so that it can support the success of students in the learning process. This research was conducted by qualitative methods, research conducted at the Future Islamic School Integrated Islamic School, with the subject of principals, teachers, educators and students. This research data was collected through observation, interviews and documentation. The results of the research that the author conducted show that the model of the procurement system of facilities and infrastructure, schools can provide a more optimal environment for the learning process of students As well as the importance of technology by involving all school staff as a means to accelerate the monitoring process, and optimize the management of infrastructure facilities, this writing is expected to be the basis for improving the governance of goods in similar schools.